2022
DOI: 10.1038/s41586-022-05311-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and genetic control in colorectal cancer evolution

Abstract: Genetic and epigenetic variation, together with transcriptional plasticity, contribute to intratumour heterogeneity1. The interplay of these biological processes and their respective contributions to tumour evolution remain unknown. Here we show that intratumour genetic ancestry only infrequently affects gene expression traits and subclonal evolution in colorectal cancer (CRC). Using spatially resolved paired whole-genome and transcriptome sequencing, we find that the majority of intratumour variation in gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 96 publications
8
73
0
Order By: Relevance
“…SDevo additionally reconstructs the probability of each spatial state (center versus edge) for the ancestors of the sampled population (plotted as pie charts on the internal nodes of Figure 3B). These reconstructions suggest that the majority of ancestors divided on the tumor edge, consistent with the findings of Househam et al (2022) and our expectations of boundary-driven growth.…”
Section: Phylodynamic Models Can Recover Signals Of Boundary-driven G...supporting
confidence: 88%
See 2 more Smart Citations
“…SDevo additionally reconstructs the probability of each spatial state (center versus edge) for the ancestors of the sampled population (plotted as pie charts on the internal nodes of Figure 3B). These reconstructions suggest that the majority of ancestors divided on the tumor edge, consistent with the findings of Househam et al (2022) and our expectations of boundary-driven growth.…”
Section: Phylodynamic Models Can Recover Signals Of Boundary-driven G...supporting
confidence: 88%
“…Similar patterns have been noted in cultured tumor spheroids ( Sutherland and Durand, 1984 ; Mueller-Klieser, 1987 ) and organoids ( Florian et al, 2019 ; Laurent et al, 2013 ). Since then, analysis of both clinical samples - via immunohistochemistry ( Hoefflin et al, 2016 ; Bastola et al, 2020 ), spatial transcriptomics ( Berglund et al, 2018 ; Wu et al, 2021a,b ) and genetic analysis ( Li et al, 2021 ; Househam et al, 2022 ) - and experimental systems such as fluorescently-tracked xenografts ( Lamprecht et al, 2017 ; Lenos et al, 2018 ; van der Heijden et al, 2019 ; Reeves et al, 2018 ), have further supported spatial heterogeneity and preferential expansion on the tumor periphery in some tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the power to detect expression changes was limited by the recurrence of a given SCAA in the cohort, incomplete matched RNA data and the lack of information about other factors influencing transcription such as methylation, post-translational modifications or trans regulation. To further probe the impact of somatic mutations on SCAAs, we analysed SNVs that we found were associated with changes in cis gene expression in our associated article 38 and found that some of these SNVs co-occurred with a change in chromatin accessibility at the locus (figures at https://doi.org/10.6084/m9.figshare.19857274).…”
Section: Impact Of Scaas On Gene Expressionmentioning
confidence: 99%
“…The basic processing of matched RNA-seq data is described in the associated manuscript 38 . A subset of 27,699 peaks that were either adjacent to a known TSS of a gene 96 or overlapped a previously characterized enhancer element described in the GeneHancer database 91 were identified.…”
Section: Identification Of Associated Changes In Gene Expressionmentioning
confidence: 99%